An Improved Distribution Network Reconfiguration Algorithm Based on Niche Discrete PSO - Chen, Yong; Chen, Shu Heng; Chen, Luan (Applied Mechanics and Materials, 2013)
Based on Niche discrete PSO method, an improved algorithm, which is applied to distribution network reconfigu-reation, is proposed. Above all, the economic assessment model of reconfiguration, which encompasses line loss, voltage quail-ty, load balance and switch acting cost, is established. Then, with Niche operations embedded into the DPSO algorithm, an improved reconfiguration method is presented. Finally, the corresponding software system is realized and this improved algorithm is applied to a typical case. The experimental results have proved that the improved Niche discrete PSO algorithm is reliable and efficient.